Real-world smartphone-based point-of-care diagnostics in primary health care to monitor HbA1c levels in people with diabetes - Sabrina Rhode; Lisa Rogge; Marthoenis Marthoenis; Till Seuring; Hendra Zufry; Till Bärnighausen; Hizir Sofyan; Jennifer Manne-Goehler; Sebastian Vollmer (Communications Medicine)
Abstract Background The lack of accurate and affordable monitoring of glycated hemoglobin (HbA1c) is a common issue among patients with diabetes in low- and middle-income countries. We aimed to test a tablet- and smartphone-based point-of-care (TSB POC) device against a local laboratory-based measure of HbA1c for monitoring diabetes under real-world conditions. Methods For this cross-sectional clinical method applicability study, capillary and venous blood was collected in duplicate and analyzed at local primary health care centers. For a heterogeneity test, the tests were performed by an expert, and by a team of local nurses. The study was conducted in a multicenter design in rural and urban Aceh, Indonesia in 2019, and included a total of 533 adults. We mainly used Bland-Altman plots to assess the number of readings within the 95%-limits of agreement (LoA) and Deming regressions. Results The results show a mean difference between capillary HbA1c on the test device and the reference method of −0.54 [CI0.95 = −1.6933; 0.6048] with 5.21% of measurements outside the LoA and a Pearson’s r = 0.91 in the Deming Regression. There is no significant difference in test concordance between local nurses and the expert (4.23% versus 5.13% results outside the LoA [CI0.95 = −0.0331; 0.0511]). Conclusions TSB POC for analysis of HbA1c is an acceptable alternative for accessible monitoring of diabetes patients under these conditions. This method could provide access to high-quality diagnostic decisions through regular and cost-effective HbA1c monitoring directly in healthcare facilities, thus providing better access to essential health services.